Community participation in community-based prevention programs; a short review of the literature on challenges to breast cancer prevention programs or activities - Ahmadian, Maryam; Abu Samah, Asnarulkhadi (Marsland Press, 2012)
This article reviews the potential of widely used psycho-social factors affecting community participation in community-based prevention programs among diverse communities. Besides, we specifically appraised the previous literature to look into the psycho-social, structural, and demographic factors which create latent challenges to community participation in breast cancer prevention programs. We believe communities with lack of behavioral and psycho-social change components are likely to have low motivations to participate in health programs against diseases such as breast cancer. Additionally, certain demographic characteristics and potential structural factors control a distinct participation in health programs. Clarification of participation in public health programs and its psycho-social, structural, and demographic attributes are keys to explicate why and how socio-cultural, behavioural, and multifaceted interventions should be main concern in the evaluation of community participation in health promotion programs. The idea here is rather to emphasize on community participation in breast cancer prevention activities for community development undertakings.